MURABAHAH CONTRACT WITH DELAYING OF HANDOVER OBJECT FOR FINANCING OF MULIA’S PROGRAM (Case Studies at Pegadaian Syariah of Bengkulu) - Alfiah, Esti (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2018)
This research find about financing of MULIA’s program programs the one of financing method with murabahah contract at Pegadaian. There goods things as a object are holded by Pegadaan. Exactly the purpose of this research is to know how ascept delays object with murabahah contract in prespective of Islamic economic. The kind of this research is descriptive qualitative, and the location at research is Pegadaian Stariah of Bengkulu. And to collect all of data are conducted by interview and documentation. Based on this research can the conclude that implementation at murabahah contract with delaying in handover of object for financing of MULIA’s program at Pegadaian Syariah Bengkulu are not suitable with prespective of Islamic economic.